A non-redundant piezoelectric center-rotation platform with a single-layer structure and a large working range. (December 2022) - Wu, Yuxi; Yang, Yiling; Li, Guoping; Cui, Yuguo; Du, Huilin; Wei, Yanding
Highlights: Single-layer center-rotation platform without actuator redundancy. Large working range and high resonant frequency. Analytical models using finite element approach. A serials of experiments and validations. Abstract: This paper reports the design, modeling, and testing of a new single-layer center-rotation platform driven by a single piezoelectric actuator. The platform avoids actuator redundancy and exhibits a large rotation angle, high-precision resolution, and high resonant frequency. The pure center- rotation motion is realized by combining the improved Scott-Russell (SR) mechanism and lever- guided structure. The auxiliary stiffness mechanism at the input end of the SR mechanism also improves the stability of the rotation platform. An analytical model is established based on the finite element method, and the key parameters affecting the structural performance are investigated. A prototype is finally manufactured, and several experiments are conducted to test the proposed platform. The experimental results show that the rotation angle is 16.8 mrad, the resonant frequency is 527.3 Hz, and the resolution is 0.29 μrad. Thus, the platform is capable of precision center rotation. Graphical abstract: Image, graphical abstract